The Political Economy of New Slavery
XVI, 272 p.
Keywords: This unique volume combines chapters containing a multidisciplinary academic analysis of the causes of the continued existence of contemporary forms of slavery, such as globalization, poverty and migration with empirical chapters on trafficking, domestic migrant workers, bonded labour and child labour in Asia, Latin America and Africa. It provides relevant policy recommendations, such as respect for victims' rights and assesses longer term strategies for change, including Fair Trade, reparations for slavery in the past, the Tobin tax and Development ethics.